P239 Genital HSV-2 suppression is not associated with alterations in the vaginal microbiome: a one-way, cross-over study. (14th July 2019) - Johnston, Christine; Magaret, Amalia; Srinivasan, Sujatha; Proll, Sean; Varon, Dana; Marrazzo, Jeanne; Fredricks, David; Wald, Anna
Abstract : Background: Women infected with herpes simplex virus type 2 (HSV-2) have increased risk of incident and refractory bacterial vaginosis (BV). We hypothesized that suppression of HSV-2 would be associated with decreased Nugent score and risk of BV. Methods: HSV-2 seropositive women with a self-reported history of BV self-collected daily vaginal and anogenital swabs for 28 days. Women then initiated valacyclovir 500 mg daily for a 2 week lead-in, followed by continued valacyclovir and self-collection of swabs for an additional 28 days. Anogenital swabs were tested for HSV DNA by PCR. Nugent score was performed on vaginal swabs (score ≥7 denoted BV). Quantitative PCR for three Lactobacillus species, Gardnerella vaginalis, Megasphaera, and BV-associated bacterium 2 was performed from DNA extracted from vaginal swabs. The primary outcome, per-participant median Nugent score at baseline compared to valacyclovir, was calculated using linear mixed models. We had 80% power to detect a 50% reduction in rate of BV on valacyclovir. Results: Forty-one women collected a median of 28 days of swabs during each study period. Thirty-three (80%) had a history of symptomatic genital HSV-2 infection, with a median of 2 self-reported recurrences in the past year (range 0–12). The genital HSV shedding rate decreased from 109 (9.7%) of 1126 days at baseline to 6 (0.05%) of 1125 days on valacyclovir (RR=0.06, 95% CI=0.02–0.13). Median Nugent score was 3.8 at baseline and 4.0 on valacyclovir (predicted change=0.26, 95% CI=-0.43–0.94). Women had BV on 343 (31.1%) of 1103 days at baseline and on 302 (27.7%) of 1091 days on valacyclovir (RR=0.90, 95% CI=0.68–1.20). Average log10 concentrations of bacterial species did not change significantly during valacyclovir treatment. Conclusion: Use of short-term valacyclovir suppression among women with HSV-2 infection did not decrease the Nugent score or risk of BV and did not change concentrations of key vaginal bacteria. Disclosure: No significant relationships.